According to the 2019 updated European League Against Rheumatism (EULAR) recommendations for the treatment of systemic lupus erythematosus: debatable issues and comments - T. V. Popkova; T. A. Panafidina; S. K. Solovyev (Научно-практическая ревматология)
A diversity of the clinical manifestations of systemic lupus erythematosus (SLE) and its undulating course with alternating remissions and exacerbations make this disease one of the most difficult ones to diagnose, treat, and evaluate the efficiency of therapy.Despite the fact that the recently developed methods for early diagnosis and procedures for combined pathogenetic therapy and monitoring  the disease course have led to increases in survival rates (≥90%) and life expectancy in patients with SLE, there are still many unsolved problems. In particular,  the treatment for SLE is not yet efficient enough and the activity of the latter cannot be completely controlled.  The relapsing and remitting course of SLE concurrent with comorbidity,  as well as the adverse effects of glucocorticoids  and immunosuppressants contribute to the accumulation of irreversible organ damages.The paper is devoted to a review of the updated EULAR recommendations for the treatment of systemic lupus erythematosus, which were published in 2019. It presents comments  and debatable issues, by taking into account the Russian recommendations for the treatment of SLE.